(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2022)
The well-preserved limestone succession, Loma Negra Formation ( 40 m), in the Tandilia System was deposited in a shallow carbonate ramp under low energy conditions. The evolution in the depositional settings of the unit was indicated as deepening upwards varying from shallow-middle to outer ramp environment. The limestone fabric is assumed as the product of biologically controlled precipitation of micrite, where the terrigenous supply was limited. From detailed meso- and microscopic descriptions it is possible to recognize microbially induced sedimentary structures ‘MISS’ represented by typical microtextures related to microbial activity that appear represented throughout the entire formation. In addition, micro-stromatolites are observed in the unit associated with the microbial mats showing micro-columnar conical to domical morphologies. In the basal and middle Loma Negra Formation, hemispherical structures are recognized in the bed-tops and interpreted as bubbles-like and gas escape features associated with the microbial mat interaction. Their morphology is compared with oxygen bubbles produced by modern experimental modelling with photosynthetic cyanobacteria microbial mats. Moreover, hemispherical structures are associated with increasing gas pressure lifting grains and the organic components to the surface. This paper provides evidence to understand the possible causal relationship between microbial activity and seawater oxygenation. The high oxygen production revealed by geochemistry proxies and here proposed as probably associated with photosynthetic microbial activity might be a plausible explanation for the record of the documented Middle Ediacaran Oceanic Oxygenation Event in the Loma Negra Formation.